Application of Proportional Integral Derivative (PID) Control in Overvoltage Protection Systems for Low Voltage Network Loads - Prasetia, Abdul Muis; Linda Sartika; Tirvan (Universitas Muhammadiyah Surakarta, 2024)
Electricity is a very essential need for every element of society in this modern era, with electricity, various kinds of work can be easily done. However, in electricity distribution, there are often disturbances that can be detrimental to consumers, One of the power lines that usually experiences interference is the Low Voltage Network (JTR) line. JTR is a transmission network with a low voltage classification between 220 volts and 280 volts. In this transmission, various kinds of disturbances often occur, such as overvoltage and voltage drops. In this research, the author discusses the overvoltage protection system using Proportional Integral Derivative (PID) control. PID control is a simple control method that several researchers have developed to overcome various electrical problems in this modern era. For this reason, the researcher will develop PID as a protection system to overcome overvoltage disturbances in JTR transmissions. The appropriate PID parameter value to overcome overvoltage in this study is the value Kp = 5; Ki = 0,3 Kd = 0.01, where the system is able to protect the overvoltage according to the setpoint value 220 volts.